Hubungan Asupan Serat, Kolesterol, Natrium dan Olahraga Dengan Kadar Kolesterol dan Hipertensi pada Lansia - magdalena magdalena (Medical Laboratory Technology Journal, 2015)
Hypercholesterolemia is an excess of cholesterol in the blood, can be factors for heart disease and stroke. The cause of hypertension is heredity, age, sex, obesity (overeating), lack of exercise, stress, excessive salt intake, another effect: smoking, alcohol consumption, taking drugs. The purpose of this study was to determine the relationship of fiber intake, cholesterol, sodium and exercise with cholesterol and hypertension in the elderly group S. Parman Banjarmasin. Type of research is descriptive analytic research using cross sectional design of the study, which was conducted in a group of elderly Regional Health Center S. Parman Banjarmasin. This research was conducted in January through June 2015 with a sample size of 50 people. The data obtained is the intake of cholesterol, sodium, exercise and cholesterol and hypertension. The statistical test used is Chi Square test (p